Elementary School Students' Ability to Solve Mathematical Story Problems - Delafia Maghfiroh, Delafia; Wahyuningsih , Retno (JENIUS :Journal of Education Policy and Elementary Education Issues, 2024)
Elementary school students' ability to solve mathematical story problems is important in implementing contextual learning in everyday life, but students often have difficulty understanding and solving story-based problems. This study analyses students' ability to solve mathematical story problems, namely conceptual understanding, operational abilities, and problem-solving. This type of research is descriptive quantitative research carried out in stages from September 2023 to April 2024. The study subjects were 34 fifth-grade students who were given five essay story problems. The data analysis technique in this study used descriptive statistics with percentages. The results showed that in the aspect of conceptual understanding, the average score of students was 2.18, with the majority of answer categories at a low level (47.05%). Regarding operational abilities, the average score reached 2.35 for multiplication and 2.32 for division operations, with the highest answer categories at a low level (35.29% and 35.29%). In the problem-solving aspect, the average student score was 1.76 for question 4 and 1.88 for question 5, with most students (58.82% and 44.11%) in the low category. Overall, the average score of students in solving story problems was 52.65, with a standard deviation of 18.80; the highest score was 90, and the lowest score was 25. These results indicate that students' ability to solve mathematical story problems still needs to be improved, especially in problem-solving. More structured learning interventions based on problem-solving steps are recommended to improve students' abilities